APPROACHES IN MEDIEVAL RESEARCH IN THE STUDY OF THE SOCIAL-RELIGION BASIS OF RELIGION AND MEDICINE (in the example of christianity and islam) - Alidzhanova Lazizakhan Abbasovna, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
The global processes taking place in the world require a harmonious approach to the issue of the mental and physical health of a person. In modern medical practice, solutions to existing problems can be found through medical-spiritual procedures based on religious teachings. In the teachings of Christianity and Islam, which are considered world religions, during many millennia of history, guidelines for regulating not only the spiritual but also the medical health of a person have been developed and are being implemented. In the context of the 2019 global pandemic related to COVID-19, the popularization of spiritual-psychological ( الروحية والنفسة ) treatment processes along with medical treatment has increased the importance of religious medicine. In this respect, the study of their religious and social foundations regarding human health issues is of urgent importance.